2015
DOI: 10.1016/j.neulet.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Inborn stress reactivity shapes adult behavioral consequences of early-life maternal separation stress

Abstract: Early-life experience strongly impacts neurodevelopment and stress susceptibility in adulthood. Maternal separation (MS), an established model of early-life adversity, has been shown to negatively impact behavioral and endocrine responses to stress in adulthood. However, the impact of MS in rats with heightened inborn stress susceptibility has not been fully explored. To address this issue we conducted MS in Wistar-Kyoto (WKY) rats, an animal model of comorbid depression and anxiety, and Wistar rats, which sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
8
41
2
Order By: Relevance
“…Stress during early development can increase either anxiety-like behavior (Brunton, 2013; Maccari et al, 2014) or resilience to stressful stimuli (Faure et al, 2007; Zhang et al, 2014; Beery and Kaufer, 2015; Rana et al, 2015) in adulthood. Studies using maternal deprivation as an early life stressor have found both increased (Ishikawa et al, 2015) and decreased anxiety in adulthood in rats (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Stress during early development can increase either anxiety-like behavior (Brunton, 2013; Maccari et al, 2014) or resilience to stressful stimuli (Faure et al, 2007; Zhang et al, 2014; Beery and Kaufer, 2015; Rana et al, 2015) in adulthood. Studies using maternal deprivation as an early life stressor have found both increased (Ishikawa et al, 2015) and decreased anxiety in adulthood in rats (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the first phase of the experiment, male/female pairs were mated for 14 days, and at birth (postnatal day 0), litters were randomly assigned to one of two groups: (i) MS‐180 group or (ii) neonatal handling (NH) group ( n = 4 L/group/strain). Litters assigned to the MS‐180 and NH groups were separated from their dam daily for 180 and 15 min, respectively, between 8:30 and 12:00 h from postnatal day (P)1–P14 as previously described (Clinton et al ., ; Rana et al ., ). Dams remained in the home cages, while separated litters were transferred to a different room in a small cage placed on a heating pad (~37 °C).…”
Section: Methodsmentioning
confidence: 97%
“…This study exploited the WKY‐MS model to identify neurobiological and epigenetic mechanisms that mediate a PAR to convey adaptive behavioral and physiological changes in adult MS‐180‐exposed WKY offspring. We hypothesized that MS‐180 triggers DNA methylation changes in the brains of WKY offspring, which may contribute to their enhanced stress resilience in adulthood (Rana et al ., ). To test this, we first examined global DNA methylation (5‐methylcytosine) levels in multiple brain regions of adult WKY rats that were exposed to MS‐180 (or control condition).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations